MELANSIA: PEMBERDAYAAN LANSIA ANTI-STRES DI PANTI WERDHA DENGAN METODE BERKEBUN TANAMAN HERBAL - Taesar Hawaij; Devi Fitri Rahayu; Fahmi Kurniahadi; Nadiyah Salsabilah; Anna Vipta Resti Mauludyani (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Health care for elderly must be aimed for maintaining a productive and healty life. Unfortunately, most of the activities carried out by the nursing home are restricted, it's causing the elderly being less activities. Planting is one of the activites that can be overcome the issue. Planting activities can be used as an intervention technique and connection to nature that is used as a therapy and rehabilitation program. The aimed of this program is to empower the elderly for stay healthy and productive through the planting of herbal plants. This program was carried out at the Tresna Werdha Social Home, Budi Mulia 3, South Jakarta which was held from June to September 2021 by blended (offline : online = 60 : 40). This program includes 10 series of activities that is consist of planting herbal plants, education, and nutrition consultation. This program was followed by 16 participant which is 13 female and 3 male elderly and including nursing home staff. Based on the results of the activity, there was a significant increase in the proportion of the elderly with a high level of spiritual well-being up to 88%. It can be concluded that Melansia is a solution in anti-stress training for elderly during the pandemic through farming herbal plant activities that are proven to reduce stress levels in the elderly, and can increase the level of spiritual well-being and physical activity of the elderly.